Corporate social responsibility and investor's intention to invest: Analyzing the role of corporate identity and corporate image - Nazakat Hussain; Basharat Javed; Muhammad Sarmad (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
This study explores the relationship between corporate social responsibility (CSR) and investor intention's to invest under the indirect mediating mechanism of corporate identity and corporate image. The data were collected in time lags under case study method by using adopted / adapted questionnaires, duly filled by graduate university students across major cities of Pakistan, The CSR activities of Samsung Company was considered by the respective students. The data analysis was performed through AMOS, and results of structure equation modeling revealed positive direct relationship between corporate social responsibility and investor's intention to invest. The indirect mediating mechanism of corporate identity and corporate image under the said relationship was also established. The study reveals theoretical and practical implications in terms of mediating roles and CSR worth in developing country, respectively. The in-depth understanding of studied variables under certain relationships is deliberated for target sector in particular and other sectors in general.
Keywords: 330; corporate social responsibility; corporate identity; corporate image; investor's intention to invest; Samsung